Understanding the consumer - Szmigin, Isabelle (Sage Publications, 2003)
Understanding the Consumer brings together marketing theory and practice in a truly consumer-centric approach. It challenges the lip service usually paid to this concept and demonstrates that a fundamental understanding of the consumer is critical to the future of effective marketing.